Knowledge and attitude of candidates to gastroplasty about perioperative: randomized clinical trial - Lívia Moreira Barros; Francisca Antônia do Vale Gomes; Flávio Neves Carneiro; Nelson Miguel Galindo Neto; Natasha Marques Frota; Joselany Áfio Caetano (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to evaluate the effectiveness of educational intervention in the knowledge and attitude of candidates for gastroplasty. Methods: randomized controlled clinical trial with 56 preoperative patients (intervention=28; control=28). The control group received routine care from the health institution and the intervention group participated in a book-mediated educational intervention. Forms were used for clinical-epidemiological characterization and evaluation of knowledge/attitude about bariatric surgery, which were reapplied seven weeks after intervention. RBR-297fzx. Results: in the pre-test there was no significant difference between the groups (p=0.254). In the post-test, the group that received verbal guidance had a mean score of 19.5 (± 6.17) and the group reading the booklet averaged 31.1 (± 2.96), p=0.000. The attitude is adequate, especially for care such as vitamin supplement intake, water intake and physical activity practice. Conclusions: the educational intervention mediated by booklet was effective in improving knowledge and attitude when compared to verbal guidance. Thus, it can be replicated during the preoperative preparation.